Manipulations of sleep‐like slow‐wave activity by noninvasive brain stimulation. Issue 5 (20th February 2022) - DiNuzzo, Mauro; Mangia, Silvia; Giove, Federico
Abstract: Sleep is a universal and evolutionarily conserved behavior among many animal species, yet we do not have a fundamental understanding of why animals need to sleep. What we do know, however, is that sleep is critical for behavioral performance during the waking period and for long‐term brain health. Here we provide an overview of some putative mechanisms that mediate the restorative effects of sleep, namely metabolic biosynthesis, fluid perfusion, and synaptic homeostasis. We then review recent experimental findings that advance the possibility of inducing sleep‐like slow‐wave activity (SWA) during wakefulness or enhance SWA during sleep in a top‐down manner using noninvasive brain stimulation. SWA induction and SWA enhancement are believed to recapitulate the beneficial effects of sleep independent of the actual state of the subjects. If confirmed, these observations will change the way in which we investigate the neural correlates of sleep, thus paving the way for comprehending and actively controlling its restorative function.